The influence of intraocular pressure and accommodation amplitude on refractive status in school-age children - Marzuqi, Ahmad Azhar; Abdullah, Aulia Abdul Hamid; Wulandari, Lely Retno; Anandita, Nanda Wahyu (Medical Faculty of Brawijaya University, Indonesia, 2025)
Introduction: Refraction is the ability of the eye to refract light, which is divided into 3 categories of refractive status (RS), namely emmetropia, myopia, and hypermetropia. Increasing age in school-age children is also accompanied by the development of intraocular pressure (IOP) and accommodation amplitude (AA) values, which are assumed to affect retinal sensitivity (RS). Therefore, this study aims to investigate the effects of partial and simultaneous interactions between age, intraocular pressure (IOP), and age-related macular degeneration (AA) on retinal sensitivity (RS) in school-age children. Methods: This cross-sectional study utilized 236 eyeballs from children aged ≤18 years who consented to participate and completed all eye examinations at the Al-Ikhlas Singosari Orphanage in Malang. Variables included age, IOP, AA, and RS converted into spherical equivalent (SE). Data analysis employed partial and simultaneous regression tests. Result: Partially, increased age, IOP, and decreased AA influenced myopia (6.6%, 33.3%, and 19.1%, respectively), while reduced age, increased IOP, and increased AA influenced hypermetropia (14.3%, 47.2%, and 12.2%). Simultaneously, these variables affected myopia RS by 0.6% and hypermetropia RS by 2.6%, though not significantly. Conclusion: Age, IOP, and AA show effects on myopia and hypermetropia RS both partially and simultaneously, but the influence is small and insignificant.